Passive transfer of affinity-purified anti-heart autoantibodies (AHA) from sera of patients with myocarditis induces experimental myocarditis in mice. (20th January 2015) - Caforio, Alida L.P.; Angelini, Annalisa; Blank, Miri; Shani, Alice; Kivity, Shaye; Goddard, Gisele; Doria, Andrea; Schiavo, Alessandro; Testolina, Martina; Bottaro, Stefania; Marcolongo, Renzo; Thiene, Gaetano; et al.
Abstract: Background: Human autoimmune myocarditis is characterized by an increased frequency of serum organ and disease-specific anti-heart autoantibodies (AHA) in affected patients. To assess whether AHA are directly pathogenic, we used the passive transfer technique of AHA from patients to normal Balb/c mice to induce an experimental myocarditis. Methods: In keeping with a classical passive transfer experiment, sera from 5 AHA positive myocarditis patients (3 male, mean age 30 ± 11 years, 3 with giant cell and 2 with lymphocytic myocarditis) were affinity purified and injected into 25 Balb/c mice. As controls, affinity purified sera from 5 healthy donors were passively transferred to 25 Balb/c mice. Further 15 control mice were injected with phosphate-buffered saline and 9 mice did not receive any injection. In all patients cardiac-specific AHA of IgG class had been previously detected by an indirect immunofluorescence (IFL) technique on cryostat sections of O blood group human heart. The animals were sacrificed after 4 weeks and the hearts were blindly examined for histological evidence of myocarditis by an expert cardiac pathologist. Results: Myocarditis was present in 13/25 (52%) of the mice which received affinity-purified IgG from patients. The findings of severe, moderate or mild myocarditis were more common in the mice which received affinity-purified IgG from patients (20%; 20% and 12%) than in control animals (2%, p = 0.01; 0%, p = 0.003; and 0%, p = 0.04 respectively). Conclusions: These findings provide a new evidence for AHA-mediated pathogenicity in human myocarditis, according to Rose–Witebsky criteria.